Arah dan Tantangan Kebijakan Pendidikan Kejuruan di Indonesia Era Industri - Bintan Aulia; Syafira Nur Fitriani; Qomaruddin Qomaruddin (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Vocational education plays a crucial role in preparing a skilled workforce that meets the demands of the labor market. Technological advances in the Industrial Revolution 4.0 era require responsive, creative, and vocational education policies that align with industrial developments. However, several studies indicate that there is still a gap between the abilities of vocational education graduates and the skills needed in the labor market. Furthermore, the implementation of vocational education policies in Indonesia is considered to be underperforming due to various structural and operational constraints. This study aims to analyze the orientation of vocational education policies in responding to the demands of the workforce, identify key challenges in policy implementation at the national level and in field practice, and evaluate their level of alignment with workforce competency needs in the Industrial Revolution 4.0 era. This study applies a qualitative approach through library research with descriptive analysis of various policy documents, scientific articles, and relevant previous research findings. The research findings indicate that vocational education policies in Indonesia still face several key challenges, including a lack of coordination between stakeholders, inadequate human resources and educational infrastructure readiness, and a suboptimal link between the education curriculum and industry needs. Thus, it is important to strengthen cooperation between the government, educational institutions, and the industrial sector so that vocational education policies can be more efficient in producing a qualified and competitive workforce. Keywords: World of Work, Policy Implementation, Vocational Education Policy, Industrial Revolution 4.0, Literature Study